Refuerzo académico y su incidencia en el rendimiento escolar de los estudiantes de segundo año de básica de la Escuela “Ecuador”, Parroquia La Unión, cantón Babahoyo, Provincia de Los Ríos - Aviles Cabrera, Mayra Mercedes (2019)
The case study work entitled: Academic reinforcement and its incidence on the school performance of second year basic students of the Ecuador school, parroquia la unión, canton Babahoyo, province of Los Rios, which was based on observing academic performance and the result of the application of pedagogical reinforcements in the group of students chosen for this case. Specifically in the monitoring of performance levels in the students of the school in question, in order to identify these performance levels that have a group of students, and be able to make a contribution with data that can be used by teachers, to achieve the best performance in their students and use an appropriate methodology with new procedures to ensure better performance. In this study, a series of techniques and instruments for data collection, direct observation, and a basic follow-up were used to obtain data on the level of performance in various partials of the students under study. For the preparation of the report, he made the objective statement, proceeding to statistically analyze the data obtained, thus being able to establish the corresponding conclusions